2007
DOI: 10.1091/mbc.e06-09-0827
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-associated Yeast mRNAs and the Biogenesis of Molecular Complexes

Abstract: The coherence of mitochondrial biogenesis relies on spatiotemporally coordinated associations of 800 -1000 proteins mostly encoded in the nuclear genome. We report the development of new quantitative analyses to assess the role of local protein translation in the construction of molecular complexes. We used real-time PCR to determine the cellular location of 112 mRNAs involved in seven mitochondrial complexes. Five typical cases were examined by an improved FISH protocol. The proteins produced in the vicinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
69
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 40 publications
(55 reference statements)
6
69
0
Order By: Relevance
“…About half of all mMPs are thought to be translated in the vicinity of mitochondria and mRNAs of this class were named mitochondrially localized mRNAs (MLRs) (Marc et al 2002). This suggested that mitochondrial protein import could be cotranslational and indicated that MLR proteins are mainly of prokaryotic origin, linked to the assembly of core complexes, and are imported principally via the TOM-TIM23 pathway (Garcia et al 2007). Puf3, an RNA-binding protein (RBP) that belongs to the Pumilio-Fbf (Puf) family and interacts with more than 150 mMPs (Gerber et al 2004), was recently shown to be involved in the transport of mMPs encoding proteins involved in respiration and translational control within the organelle; and the loss of PUF3 gene expression influenced mRNA association with the mitochondria (SaintGeorges et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…About half of all mMPs are thought to be translated in the vicinity of mitochondria and mRNAs of this class were named mitochondrially localized mRNAs (MLRs) (Marc et al 2002). This suggested that mitochondrial protein import could be cotranslational and indicated that MLR proteins are mainly of prokaryotic origin, linked to the assembly of core complexes, and are imported principally via the TOM-TIM23 pathway (Garcia et al 2007). Puf3, an RNA-binding protein (RBP) that belongs to the Pumilio-Fbf (Puf) family and interacts with more than 150 mMPs (Gerber et al 2004), was recently shown to be involved in the transport of mMPs encoding proteins involved in respiration and translational control within the organelle; and the loss of PUF3 gene expression influenced mRNA association with the mitochondria (SaintGeorges et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These studies where then corroborated in vivo by work on specific mRNAs, that were found to be imported only in a cotranslational manner 6,7 . Genome-wide studies of mRNAs association with mitochondria revealed that a significant fraction of mRNAs are localized to the mitochondria vicinity [8][9][10] . Some of these mRNAs were further characterized by in vivo fluorescence methods, such as FISH or mTAG 9,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide studies of mRNAs association with mitochondria revealed that a significant fraction of mRNAs are localized to the mitochondria vicinity [8][9][10] . Some of these mRNAs were further characterized by in vivo fluorescence methods, such as FISH or mTAG 9,11 . A straight-forward interpretation of this association is that these mRNAs serve as templates for localized translation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the lifetime of fluorescent reporter proteins is typically not the same as the protein it is reporting, the applicability of fluorescent reporter proteins to study transcription repression is limited. Singlemolecule RNA FISH has been applied to yeast before to address a wide variety of transcription and cell-to-cell heterogeneity-related questions [27][28][29][30][31][32][33][34] .…”
mentioning
confidence: 99%